Age as risk factors associated in the genesis of uterovaginal prolapse (UVP) - Pandit, Upendra; Malla, Dibya Shree; Sharma, Paban Kumar (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: To find out the relationship between utero-vaginal prolapse (UVP) and first vaginal birth at younger age